2015
DOI: 10.1016/j.gore.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Lumbee Native American ancestry and the incidence of aggressive histologic subtypes of endometrial cancer

Abstract: ObjectiveThe Lumbee Indian tribe is the largest Native American tribe in North Carolina, with about 55,000 enrolled members who mostly reside in southeastern counties. We evaluated whether Lumbee heritage is associated with high-risk histologic subtypes of endometrial cancer.MethodsWe retrospectively analyzed the available records from IRB-approved endometrial cancer databases at two institutions of patients of Lumbee descent (year of diagnosis range 1980–2014). Each Lumbee case was matched by age, year of dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The majority of the families included in this study were of known African, Afro‐Caribbean, or Middle Eastern descent. The descent of the Lumbee Native American tribe is controversial, but has been speculated to include an admixture of Native Americans, European settlers, and African Americans (Zhang et al., ). The observation of the NAM variant in various populations often of African descent could point toward a common ancestor of possible African origin.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the families included in this study were of known African, Afro‐Caribbean, or Middle Eastern descent. The descent of the Lumbee Native American tribe is controversial, but has been speculated to include an admixture of Native Americans, European settlers, and African Americans (Zhang et al., ). The observation of the NAM variant in various populations often of African descent could point toward a common ancestor of possible African origin.…”
Section: Discussionmentioning
confidence: 99%
“…We find two clear trends. At least four of the names — “Chavis”, “Locklear”, “Oxendine”, and “Brayboy” — are traditional Native American surnames associated with the Lumbee tribe in North Carolina 18 . Individuals with these surnames are frequently categorized by the Census in the Other category, while they are overwhelmingly categorized as either White or Black on the voter file.…”
Section: Technical Validationmentioning
confidence: 99%
“…25 A small, retrospective cohort study of high-risk endometrial cancer subtypes in women of Lumbee Native American ancestry found no association between such ancestry and worse overall or disease-specific survival. 26…”
Section: Asian/pacific Islander Womenmentioning
confidence: 99%